Bridges and Tunnels - Butterworth, Christine (New York Oxford University Press, 2001)
Presents a set of information books on a topical subject for guided, shared or independent reading, with cross-curricular links. These books offer the text types required by the National Literacy Strategy - discussion, persuasion, instructions, and report. The topics are: "Cars - For and Against", "Making Moving Models" and "Bridges and Tunnels".
Include Color Illustrations
Keywords: Tunnels -- Bridges -- Readers (Elementary)